ANALISIS JALUR PENGARUH TEKNIK HITUNG VEDIC MATH, SUKU MAYA, DAN CHUNKING TERHADAP PERHITUNGAN AKAR KUADRAT METODE BABILONIA - Endro Tri Susdarwono (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
The purpose of this research is to discuss how the influence of several calculation techniques that exist both in the west and in the east, especially the Vedic Math, Maya, Chunking and Square Root Babylonian methods based on the use of path analysis. The approach in this research uses a descriptive approach, the method used is quantitative methods. The quantitative approach uses statistical tests with path analysis to answer the relationship and influence between the 4 variables. From the results of the path analysis, it is found that there is an effect of X1 (mastery of addition and subtraction with Vedic Math), X2 (mastery of multiplication by the Mayan tribe), X3 (mastery of division using the Chunking Method) on X3 (mastery of calculating square roots with Babylonian Middle Iteration). The total effect is 0.887, The total effect of 0.887 shows that the influence of Vedic Math's control of addition and control, mastery of the multiplication of the Maya method, and mastery of the division of the Chunking method based on path analysis have a joint effect on students' ability to calculate questions related to the square root of the Babylonian middle iteration technique.